2020
DOI: 10.3390/ijgi9010037
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spatial Context Information in the Generalization of Geographic Information: Using Reducts to Indicate Relevant Attributes

Abstract: Generalization of geographic information enables cognition and understanding not only of objects and phenomena located in space but also the relations and processes between them. The automation of this process requires formalization of cartographic knowledge, including information on the spatial context of objects. However, the question remains which information is crucial to the decisions regarding the generalization (in this paper: selection) of objects. The article presents and compares the usability of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Since cartographic generalization necessarily involves consideration of many criteria, this approach may simulate choices made by experts. Fiedukowicz [3] compares different variations of fuzzy and rough set theory to determine attributes that can be used for automatic selection or omission of roads, buildings and watercourses on small-scale maps. Focusing on the concept of reducts (subsets of attributes that are sufficient for discriminating between features selected vs. omitted by experts), it is shown that some variations of fuzzy or rough sets can better identify core attributes than others.…”
mentioning
confidence: 99%
“…Since cartographic generalization necessarily involves consideration of many criteria, this approach may simulate choices made by experts. Fiedukowicz [3] compares different variations of fuzzy and rough set theory to determine attributes that can be used for automatic selection or omission of roads, buildings and watercourses on small-scale maps. Focusing on the concept of reducts (subsets of attributes that are sufficient for discriminating between features selected vs. omitted by experts), it is shown that some variations of fuzzy or rough sets can better identify core attributes than others.…”
mentioning
confidence: 99%